City girl eaudiobook Yellow rose series, book 3. - Wick, Lori (Yellow Rose Trilogy, 2015)
In the late 1800s, the adventurous Reagan Sullivan leaves the bustle of New York City and moves to the wide open spaces of Texas, to work as a nanny. Fiercely independent and headstrong, she trusts no man - not even God. But when Reagan meets Cash Rawlings, she embarks on an adventure she never anticipated. As they have many conversations about spirituality, her fears miraculously melt away, and she opens up her heart to Christ. Christian fiction writer Lori Wick delights readers with her talent for creating best-selling romances based on Christian principles. City Girl completes The Yellow Rose Trilogy. Narrator Ed Sala exquisitely shares the inspirational message of faith and gratitude.